How Do Urbanization, Urban Agglomeration, and Largest City Ratio Affect Co2 Emissions? Investigating Non-Linearity Dynamic STIRPAT (Stochastic Impacts By Regression on Population, Affluence, and Technology) Model in 10 Asian Economies - Lubis, Lia Agustiana; Widodo, Wahyu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study investigates how do urbanization, urban agglomeration, and largest city ratio affect CO2 emissions in 10 Asian Economies namely Bangladesh, India, Pakistan, Nepal, China, Indonesia, Malaysia, Thailand, the Philippines and Vietnam over the period 1990- 2020. Based on STIRPAT (Stochastic Impacts by Regression on Population, Affluence, and Technology) framework, we applied dynamic seemingly unrelated regression (DSUR) to establish long-run term effects. The empirical findings revealed that urbanization and urban agglomeration have inverted U shaped effect, meanwhile largest city ratio have U shaped. Urbanization and urban agglomeration improve environment quality in the long term and supports ecological modernization theory. Urbanization and urban agglomeration improves environmental quality after reaching a significant level of urban development due to efficient energy structures, population awareness, environmentally friendly technologies, and strict urban and environmental policies. However, the finding of largest city ratio revealed U shaped. This result rejects compact city theory. It implies that excessive concentration in the largest cities have severely affected the environmental quality and violates the notion of compact-city efficiencies which could be attributed to extreme population density, overcrowding, traffic congestion and extensive demand for energy consumption. The results of the panel granger causality approach unveil bidirectional causality in urban agglomeration and its quadaratic term of urban agglomeration, largest city ratio, and quadaratic term of largest city ratio on CO2 emissions. Bidirectional causality also found in GDP and CO2 emissions. Meanwhile, unidirectional causality found in energy intensity and CO2 emissions, trade openness and CO2 emissions, financial development and CO2 emissions, as well as urbanization and CO2 emissions. The current study has implications for policymakers and respective governments to green urban infrastructures, eco-friendly dwellings, smart cities, country-specific trade policies, and renewable energy options and to adhere more stringent urban planning to improve the environmental quality.